Kajian Persepsi Masyarakat Gorontalo Terhadap Modernisasi Tradisi Tumbilotohe - Usman , Irvan; Dunggio, Mohammad Rizki B; Ibrahim, Muthmainnah; Prawesti Andini, Ika; Karim , Anisa Rafanda (Psikodinamika: Jurnal Literasi Psikologi, 2024)
The tumbilotohe tradition is one of the traditions that is characteristic of the Gorontalo area. This tradition is carried out three days before Eid al-Fitr, or to be precise on the 27th, 28th and 29th of Ramadan. As time goes by, the tumbilotohe tradition continues to change due to modernization. So this research aims to minimize the gap in perception so that the people of Gorontalo can maintain the tumbilotohe tradition amidst the current of modernization. This study used qualitative research methods. The sample in this research was determined using a purposive sampling technique. Data collection techniques in this research were carried out using open questionnaires, observation, interviews and documentation. The data in this research was then analyzed descriptively qualitatively. There is no gap between individuals in perceiving the original meaning of the tumbilotohe tradition. However, there are gaps in society in their actions. This is due to the scarcity of tools and materials and the increasingly expensive price of kerosene, ultimately forcing them to continue using led lights as a result of modernization.